Redescription of Leptolalax gracilis (Günther, 1872) from Borneo and taxonomic status of two populations of Leptolalax (Anura: Megophryidae) from Peninsular Malaysia - Dehling, J. Maximilian (Zootaxa, 2012)
A number of populations of Leptolalax from Borneo and Peninsular Malaysia have been assigned to Leptolalax gracilis in thepast, rendering it a supposedly morphologically variable and widespread species. Whereas some of the Bornean populationshave since been described as distinct species, many lowland populations from Borneo and montane populations from Peninsu-lar Malaysia remain assigned to L. gracilis. Several distinct species appear to be hidden under this nominal taxon. In order toresolve the identity of L. gracilis and clarify the character states and their variation within the topotypic population, the speciesis redescribed based on examination of the holotype and recently collected topotypic material. Furthermore, the taxonomic sta-tus of two populations from Peninsular Malaysia (Gunung Benom, Gunung Tahan) that have been assigned to L. gracilis isreassessed. Reexamination of the corresponding vouchers revealed strong morphological differences between the two popula-tions and between each population and L. gracilis from Borneo. The population from Gunung Benom differs from all species ofthe genus and is apparently undescribed. The population from Gunung Tahan is represented only by two not fully metamor-phosed juveniles and cannot be assigned unambiguously to any of the described species of the genus. It is possibly another undescribed species but more specimens, especially adults, need to be collected.